Finite element model for brick walls post-tensioned by external steel bars - Nijem, Khalil. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1982., 1982)
A finite element model was developed to study the behavior of masonry walls externally post-tensioned by vertical steel bars under lateral loading in the plane of the wall. Material non-linearity of mortar and non-linearity due to failure of mortar joints and splitting of bricks are taken into consideration. Both the cracking pattern Bnd post-cracking behavior can be studied. Comparison witb analysis of unreinforced masonry wall was done. Itis concluded that the model gives realistic prediction about tbe behavior of walls since analysis results conform to tbe expected bebavior, in that, with post-tensioning the cracking strength, stiffness and post-cracking load capacity increased, and under service loads tensile stresses decreasead significantly.
Keywords: Finite element method.; Brick walls.; Steel bars.; Masonry.